Comparison of clinical efficacy and psychological outcomes of femoral neck system combined with rhBMP-2 for young adult femoral neck fractures - Dan Li; Wanrong Yang (Frontiers in Surgery, 2026)
Objective This study aimed to compare postoperative clinical efficacy and psychological status between isolated Femoral Neck System (FNS) fixation and FNS combined with local recombinant human bone morphogenetic protein-2 (rhBMP-2) implantation in patients aged 18–55 years with unstable femoral neck fractures. Methods A retrospective clinical analysis was performed on 65 patients aged 18–55 years admitted to our institution from January 1, 2022 to December 1, 2023. All participants were divided into two treatment groups: Group A received FNS internal fixation alone, while Group B underwent FNS fixation combined with intraoperative rhBMP-2 implantation at the fracture gap. Intraoperative indicators including operative duration, fluoroscopy frequency and intraoperative blood loss were recorded. Preoperative and final follow-up Self-Rating Depression Scale (SDS) and Self-Rating Anxiety Scale (SAS) scores were collected for psychological assessment. Long-term postoperative complications, fracture healing progress, femoral neck shortening and bilateral femoral offset differences were also compared between cohorts. Postoperative radiographs were applied to evaluate fracture reduction quality and internal fixation positioning, and the Harris Hip Score (HHS) was adopted to quantify postoperative hip joint function. Results The overall follow-up period spanned 6 to 35 months, with an average follow up duration of 25.11 ± 7.35 months. The age range of subjects was 23–53 years, with an upper age limit of 55 years defined as the cut-off for young adult patients in this study. No statistically significant intergroup differences were detected in operative time, intraoperative blood loss or fluoroscopy frequency ( P > 0.05). In Group A, six patients developed avascular necrosis of the femoral head, three experienced femoral neck shortening, and two suffered fracture nonunion. At the final follow up, significant bilateral discrepancies in femoral neck length and femoral offset remained relative to the uninjured hip ( P < 0.05). In Group B, only one case of femoral head necrosis, two cases of femoral neck shortening and one case of fracture nonunion were identified, with no statistically significant bilateral differences in femoral neck shortening or femoral offset at the last follow up ( P > 0.05). Both groups demonstrated obvious postoperative declines in SDS and SAS scores, yet no between group disparity was found in final Harris hip functional scores ( P > 0.05). Conclusions FNS combined with local rhBMP-2 implantation was associated with shorter fracture healing time, lower complication rates, and improved radiographic outcomes compared with FNS alone, while hip function remained comparable between groups. Both groups demonstrated significant postoperative reductions in SDS and SAS scores.